Pinoy guide to the Big Apple - Alejandro, Reynaldo Gamboa (Vera-Reyes, 1992)
This is a guidebook to New York for Filipinos. It has information from arrival to settling down in the city. Its eleven chapters contain a lot of tips and a little humor, arranged essay style, for everything from what train to take from the airport to Manhattan, to which personal fitness trainer would be right for you. Caters to different types of Filipinos: immigrants, students, tourists, businessmen, TNTs. It contains information that would not usually be found in other guidebooks, such as the proper manner of walking to New York City! It is also has a directory as well as schedule of events and price list for almost all the places and things a New Yorker needs every day. Some data may need to be revised or updated, but this is a compact and handy guide that is very useful for Filipinos who will visit or plan to live in New York.